Prospek Agribisnis Kopi Gayo - Muhammad Buchari Sibuea (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The coffee plant is one that requires an anual commodities very long time to produce the usual cultivated in almost every tropicalcontries including Indonesia. Part of robusta coffee farmers plant species, but farmers in Central Aceh Arabica coffee pursue preciselythis area became known as the largest producer of arabica coffee in Indonesia.  From The research result obtained Gayo coffee that was derived fromCentral Aceh is a spesialty coffee that has a market share of unique and disctintive. Tecnically this area is very suitable to Although it is recognized that during this very  often a high price fluctuations, but in practice the demand for coffee is always stable and tends to increase because actually when compared to robusta coffee is arabica coffee account for 70 percent of the world coffee market.It is therefore recommended to all stakeholders espesially the goverment , in order to give more serious attention, especially on the innovationaspect of planting and other supporting policies such as provision of capital and production facilities. Found that many foreign investor have flocket to this area to invest given the distinctiveness of this coffee is not found in other areas. it is hoped that the government and related institutions working to protectthe commodity gayo coffee as a commodityof Central Aceh's special because until recently trademarked gayo coffee is still owned by theDutch that their bargaining position than the farmers are very week.Kata kunci : Agribusiness, Gayo Coffee